Influence Of Innovation Strategy Model To Improving Organizational Performance Regional Government In Indonesia - Mauladi, Andri; Rahayu, Agus; Wibowo, Lili Adi; Sofia, Alfira (Universitas Dharma Wacana, 2024)
This research is aimed at testing the innovation strategy model to improving organizational performance regional government in Indonesia The performance of the Regional Government organization is the overall achievement of the results that have been achieved and achieved in handling all activities carried out by the Regional Government in a certain period (Muhamad F., 2009) as well as a description of the achievement of the government's goals and objectives as an elaboration of the vision, mission and strategy The following agencies indicate the level of success or failure in implementing activities determined by the Regional Government in accordance with established programs and policies. And this research uses the Partial Least Squares Structural Equation Modeling analysis technique (PLS-SEM), to model many variables in research.